Meta-Synthesis: Mathematical Problem-Solving Ability Reviewed from Students’ Self-Efficacy - Erina Nurhalisha; Zaenuri Zaenuri; Kristina Wijayanti; Scolastika Mariani; Isnaini Rosyida (Universitas Teknokrat Indonesia, 2025)
Mathematical problem-solving ability is essential for individuals who study mathematics. Low mathematical problem-solving ability will result in low-quality human resources. The cause of low mathematical problem-solving ability is the lack of intensity of students doing exercises to work on mathematical problems. Mathematical problem-solving ability is closely related to students' self-efficacy. This study describes self-efficacy toward mathematical problem-solving ability, especially in mathematics learning. The method used in this study is meta-synthesis in the form of a qualitative systematic study, namely by analyzing four articles relevant to the study's title. The initial steps taken are (1) determining the questions to be studied, (2) looking for articles related to self-efficacy and mathematical problem-solving ability with a period of 2019-2024, (3) screening and selecting appropriate research articles, (4) Conducting analysis and synthesis of qualitative findings, (5) implementing quality control, and (6) concluding the final results. The analysis results concluded that self-efficacy affects students' mathematical problem-solving ability. The higher the self-efficacy, the better the ability to build mathematical knowledge through problem-solving (what is known and what is asked), the ability to solve problems that arise in mathematics and other contexts, the ability to apply and use various appropriate strategies to solve problems, and the ability to observe and reflect on the process of solving mathematical problems.